2016
DOI: 10.1038/srep32912
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically activated artificial cell by using microfluidics

Abstract: All living organisms sense mechanical forces. Engineering mechanosensitive artificial cell through bottom-up in vitro reconstitution offers a way to understand how mixtures of macromolecules assemble and organize into a complex system that responds to forces. We use stable double emulsion droplets (aqueous/oil/aqueous) to prototype mechanosensitive artificial cells. In order to demonstrate mechanosensation in artificial cells, we develop a novel microfluidic device that is capable of trapping double emulsions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…We have previously used this approach and showed that small molecules from the feeding solution can enter encapsulated vesicles containing integrated synthesis, assembly, and translation (iSAT) reactions 10 . We have also shown that Ca 2+ can enter a double emulsion droplet with an ultrathin oil layer as the middle phase when the droplet is under hypo-osmotic shock 24 . However, Ca 2+ as a charged ion cannot across a lipid bilayer.…”
mentioning
confidence: 76%
“…We have previously used this approach and showed that small molecules from the feeding solution can enter encapsulated vesicles containing integrated synthesis, assembly, and translation (iSAT) reactions 10 . We have also shown that Ca 2+ can enter a double emulsion droplet with an ultrathin oil layer as the middle phase when the droplet is under hypo-osmotic shock 24 . However, Ca 2+ as a charged ion cannot across a lipid bilayer.…”
mentioning
confidence: 76%
“…The microfluidic device is designed to trap single cells in different chambers, confine cell spreading on microcontact printed islands, and apply planar compression onto the cells. The device consists of two layers, the flow layer (magenta) and the control layer (blue and orange) (Figure 1A ), similar to the previously designed microfluidic device in our group (Ho et al, 2016 ). The flow layer has a comparable design, where fluid and cells flow from two inlets through the microfluidic channel to one outlet.…”
Section: Methodsmentioning
confidence: 93%
“…Our lab previously developed a microfluidic aspiration and compression device and demonstrated compression of double emulsion droplets (Ho et al, 2016 ). However, there were two critical challenges that prevented the use of the same device for single-cell compression.…”
Section: Introductionmentioning
confidence: 99%
“…Both cell aspiration to increase cell tension and mechanical compression to single cells are possible with microfluidic devices. 143 , 144 Finally, recent microfluidic systems aim to recapitulate more physiological conditions have been developed by creating more complex co-culture models that uses vacuum to produce cyclic stretching to imitate lung expansion 145 or using optically excitable ion channels to simulate neuromuscular junctions. 146 Microfluidic systems with precise control have made an impact on cell–ECM research in recent years and readers are referred to more comprehensive, excellent overviews of microfluidic platforms for mechanobiology research and 3D culture systems.…”
Section: Microtechnologies In Research On Cell–ecm Interactionmentioning
confidence: 99%